Increase in Short-Interval Intracortical Facilitation of the Motor Cortex after Low-Frequency Repetitive Magnetic Stimulation of the Unaffected Hemisphere in the Subacute Phase after Stroke - Eduardo Arruda Mello; Leonardo G. Cohen; Sarah Monteiro dos Anjos; Juliana Conti; Karina Nocelo F. Andrade; Fernanda Tovar Moll; Theo Marins; Corina A. Fernandes; Waldyr Rodrigues; Adriana Bastos Conforto (Neural Plasticity)
Low-frequency repetitive transcranial magnetic stimulation of the unaffected hemisphere (UH-LF-rTMS) in patients with stroke can decrease interhemispheric inhibition from the unaffected to the affected hemisphere and improve hand dexterity and strength of the paretic hand. The objective of this proof-of-principle study was to explore, for the first time, effects of UH-LF-rTMS as add-on therapy to motor rehabilitation on short-term intracortical inhibition (SICI) and intracortical facilitation (ICF) of the motor cortex of the unaffected hemisphere (M1UH) in patients with ischemic stroke. Eighteen patients were randomized to receive, immediately before rehabilitation treatment, either active or sham UH-LF-rTMS, during two weeks. Resting motor threshold (rMT), SICI, and ICF were measured in M1UH before the first session and after the last session of treatment. There was a significant increase in ICF in the active group compared to the sham group after treatment, and there was no significant differences in changes in rMT or SICI. ICF is a measure of intracortical synaptic excitability, with a relative contribution of spinal mechanisms. ICF is typically upregulated by glutamatergic agonists and downregulated by gabaergic antagonists. The observed increase in ICF in the active group, in this hypothesis-generating study, may be related to M1UH reorganization induced by UH-LF-rTMS.